GEORIS Pavers – A Small Scale Demonstration Within the GEORIS Project - Potrč, Sanja; Bogataj, Miloš; Kravanja, Zdravko; Novak Pintarič, Zorka; Marina Bajić (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
Technology of alkali activation is an alternative sustainable approach to producing paving paver, where reactive aluminosilicate precursor undergoes a reaction with an alkaline solution to form binded product. The case study presents the functional usability of a technology as part of the Georis project. The construction pavers are composed of over 75% industrial residues, with the majority of the materials sourced from steel slag industry. Laboratory testing of pavers confirmed the promising mechanical properties, demonstrating high compressive and flexural strength, as well as resistance to frost and abrasion. The results support the feasibility of scaling up from lab-scale to pilot manufacturing. The innovative approach in this project was the pilot production process itself, where more than 20 m² of pavers were manufactured and cured in a mobile unit. To assess their real-world performance, a demonstration case was implemented at the SIJ Acroni courtyard, where the pavers were installed to observe their application in a practical setting and to monitor their long-term durability. The valorisation of residues within GEORIS pavers highlights lower CO₂ emissions compared to conventional cement-based pavers and the potential of technology for industrial symbiosis and circular economy initiatives, making it an attractive solution for environmentally conscious industries.